Eleanor’s Power in Crazy Rich Asian - Oneptin Kurnia Tandisau; Andi Febriana Tamrin (HUMAN: South Asian Journal of Social Studies, 2021)
Women are a part of society, but sometimes their position is unequal. This modern era a person’s position in society is generally based on how much its material. A person’s wealth greatly influences the environment without exception for women. The purposes of this research are to reveal the effect that happens to society from Eleanor’s power and to find out the way of Eleanor deal with her social stratification problem. The theory used in this research is Weberian stratification. Weberian stratification is depicted three class systems which are status, economic and party. The qualitative research methodology is applied to analyze data. Instrument of the data collection is note taking. The results of this research showed that the effect of Eleanor’s power as domination made her becoming a leader, the effect of her power as contributed made her becoming independent and the effect of her power as empowerment made her society to feel the impact that she has.Keywords: Weberian stratification, Eleanor, women’s power